Determinasi Psikologis dalam Keputusan Reinvestasi Meme Coin: Studi Empiris pada Chain Solona - Johan Pratama Siahainenia; I Gusti Bagus Yosia Wiryakusuma; Rhema Angela Krisandy; Jeremy Misael Mulyono (Universitas Muhammadiyah Palembang, 2026)
This study aims to analyze the influence of autonomous motivation, cognitive reappraisal, and sense of belonging on reinvestment intentions in speculative digital assets, specifically meme coins. This study uses the Self-Determination Theory framework to understand how motivational factors, emotional regulation, and social attachment influence young people's investment decisions in the digital space. The research method employed a quantitative approach by distributing questionnaires to 180 young investor respondents who actively invest in meme coins on the Solana chain. Data analysis was conducted using multiple linear regression. The results showed that autonomous motivation and sense of belonging had a positive and significant effect on reinvestment intentions, while cognitive reappraisal had no significant effect. These findings confirm that digital investment decisions are more influenced by personal value alignment and social attachment than by emotional reinterpretation. Theoretically, this study extends the application of Self-Determination Theory in the context of behavioral finance by highlighting the importance of intrinsic motivation and social relationships in digital financial behavior. Practically, these results recommend the need to develop financial literacy and emotional intelligence in young investors so they can manage risk and maintain psychological stability in the face of crypto market volatility.